O jornal na perspectiva semiótica: o caso do ônibus 174 e o caso Eloá - Cava, Ana Cecília dos Santos (Universidade Federal de São Carlos, 2021)
This work of conclusion of course aims to reflect on the passionate dimension created by the newspapers, from the analysis of the news of two events that had national repercussion, leading to the performance of all journalistic vehicles. For this, we surveyed the news about the cases in the newspaper Folha de S. Paulo and selected those that dealt with moments that we evaluated as crucial to the created narrative. The selected news were analyzed based, mainly, on the contributions of Algirdas Julius Greimas and other authors of semiotics of French origin, who are interested in the relations between the content plan and the expression plan, as well as a semiotic of affections and passions. This allowed us to realize that in both news there is exploration of the complex passion of cholera, as well as a game between objectivity and subjectivity effects, from certain uses of linguistic and semiotic resources. We hope that our work can be a contribution, on the one hand, to the semiotic studies of journalistic texts and, on the other, to contemporary society in general, since we intend to show how certain textual and discursive structures of the news are elaborated.
The newspaper from a semiotic perspective: the case of bus 174 and the case of Eloá
Keywords: Semiótica discursiva; Jornal online; Semiótica das paixões; Semiotics; Greimas; Newspapers; Passions; LINGUISTICA, LETRAS E ARTES::LINGUISTICA